Performance-based seismic assessment method for Taiwanese historic Dieh-Dou timber structures. - Tsai, Pin-Hui
Lateral force, response spectrum and step-by-step pushover analyses are performed and compared with the post-earthquake survey of two Dieh-Dou buildings seriously affected in the 1999 Chi-Chi earthquake in Taiwan. The results show that the proposed FE model with finite translational and rotational stiffness can successfully be employed to assess the vulnerability of the frames. The fundamental period of Dieh-Dou structures is about 1.0 s higher than that calculated by the simplified approach of the codes for regular frames; a modal analysis is, therefore, essential for this typology of structure. The elastic analysis, either lateral force or response spectrum, is shown to be reliable to assess Dieh-Dou frames when quick results are desired. However, a non-linear step-by-step pushover analysis has the advantage of greater accuracy, as it allows mapping the failure trend and indicating the critical elements. The lateral drifts are compared with the actual observed damage pattern and when the damage level is related to the peak ground acceleration on a vulnerability curve plot, it is shown that the joint failure combined with the lateral drift gives an indication of the global structural behaviour of this historic construction typology. Owing to the unique construction features of the Dieh-Dou, the joint failure represents also a critical criterion in terms of maximum retention for conservation. Based on a damage level approach, an assessment methodology is suggested that would allow optimizing a strengthening strategy, for protection of these precious structures from future earthquakes while avoiding unnecessary interventions.
Keywords: Performance-based assessment; Historic timber structures; Strengthening